Fantasy and belief alternative religions, popular narratives and digital cultures - Kirby, Danielle, 1980- (Abingdon, Oxon ; New York : Routledge, 2014)
"Religion and spirituality are being transformed in our late modern and secularising times. New forms of belief proliferate, often notable for not being limited to traditional systems of reference or expression. Increasingly, these new religions present worldviews which draw directly upon popular culture - or occulture - in fiction, film, art and the internet. Fantasy and Belief explores the context and implications of these types of beliefs through the example of the Otherkin community. The Otherkin are a loosely-affiliated group who believe themselves to be in some way more than just human, their non-humanity often rooted in the characters and narratives of popular fantasy and science fiction. Challenging much current sociological thinking about spirituality and consumption, Fantasy and Belief reveals how popular occulture operates to recycle, develop, and disseminate metaphysical ideas, and how the popular and the sacred are combining in new ways in today's world."--Publisher's description.
Religion, occulture, and the modern world -- Otherkin -- Fantasy and reenchantment -- Internet and popular cultures -- Conclusions -- Appendix 1: glossary -- Appendix 2: otherkin survey results.
Originally published: Equinox Ltd., 2015.
Includes bibliographical references and index.
Print version record.
Keywords: Religion and culture; Mass media -- Religious aspects; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books